Penerapan Total Quality Management (TQM) Dalam Meningkatkan Kualitas Pengelolaan Keuangan Bawaslu Kabupaten Enrekang: Penelitian - Rahmah Khairunnisa Binti Baharuddin; Riswan R Syam; Suriyati; Mahfud Nurnajamuddin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the implementation of Total Quality Management(TQM) in improving the quality of financial management at the Election Supervisory Body (Bawaslu) of Enrekang Regency as a public sector institution required to ensure accountability and transparency. The study employs a descriptive qualitative approach using a case study method, with data collected through interviews, observations, and analysis of financial documents, focusing on key TQM principles, including customer focus, continuous improvement, and employee involvement. The findings indicate that the gradual implementation of TQM has a positive impact on operational efficiency, administrative orderliness, and the accountability of financial reporting. However, the comprehensive implementation of TQM still faces challenges, particularly regarding the consistency of leadership commitment and the strengthening of a culture of continuous improvement across all organizational levels.